2021
DOI: 10.2807/1560-7917.es.2021.26.43.2100978
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale outbreak of hand, foot and mouth disease, France, as at 28 September 2021

Abstract: We report a large-scale outbreak of hand, foot and mouth disease (HFMD) in France. As at 28 September 2021, 3,403 cases have been reported (47% higher than in 2018–19). We prospectively analysed 210 clinical samples; 190 (90.5%) were enterovirus-positive. Most children presented with atypical HFMD. Coxsackievirus (CV)A6 (49.5%; 94/190) was predominant; no enterovirus A71 was detected. Dermatological and neurological complications of HFMD justify prospective syndromic and virological surveillance for early dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…For enteroviral infections, the association between the laboratory of the National Reference Centre for enteroviruses and the PARI network reported a large-scale outbreak of hand, foot and mouth disease and herpangina in 2021. 16 In a subgroup of children, clinical diagnoses by pediatricians of the PARI network were confirmed by PCR in 90·5% of cases, attesting to the accuracy of clinical diagnosis. 16 The increase of gastroenteritis cases in France in comparison with other countries is probably associated with the fact that vaccination against rotavirus was not recommended in France and immunity debt could not thusly be attenuated by vaccine program.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For enteroviral infections, the association between the laboratory of the National Reference Centre for enteroviruses and the PARI network reported a large-scale outbreak of hand, foot and mouth disease and herpangina in 2021. 16 In a subgroup of children, clinical diagnoses by pediatricians of the PARI network were confirmed by PCR in 90·5% of cases, attesting to the accuracy of clinical diagnosis. 16 The increase of gastroenteritis cases in France in comparison with other countries is probably associated with the fact that vaccination against rotavirus was not recommended in France and immunity debt could not thusly be attenuated by vaccine program.…”
Section: Discussionmentioning
confidence: 82%
“… 8 , 9 , 10 Various studies have reported a marked increase in the incidence of different diseases in 2021, supporting the relevance of the concept of immunity debt for RSV and enterovirus. 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…NPIs helped control the source of infection, prevented transmission and protected susceptible people; they might have also had an important effect on other communicable diseases such as HFMD in addition to COVID-19, consequently leading to a greater susceptibility to infections in children [ 9 , 10 ]. This phenomenon has also been observed in other countries such as recently reported outbreak of HFMD in France in September 2021, respiratory syncytial virus (RSV) infections in Japan in July 2021 and Europe, which was substantially larger and earlier compared with previous years [10] . In Sao Paulo State, HFMD outbreaks began soon after the gradual easing of NPIs by Brazilian government authorities.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread circulation of NPEV, the epidemic pattern of EV infections and the recent types EV involved in severe neurological conditions warrant reinforcement of the surveillance of EV infections [10] . This study shows that a syndromic and laboratorial surveillance network are of value for timely detect outbreaks HFMD, monitor circulating emergent types EV, and recommend control measures that prevent and contain the spread of disease.…”
Section: Discussionmentioning
confidence: 99%
“…After these two outbreaks, several CVA6 upsurges were reported worldwide [ 3 , 4 , 5 , 6 , 7 ]. CVA6 was mainly involved in sporadic disease cases of herpangina (HA), but mounting evidence points to its capacity to cause large seasonal outbreaks of HFMD [ 8 ] associated with atypical presentations including vesiculobullous eruption [ 9 , 10 , 11 ], adult cases [ 12 , 13 , 14 ], and neurological manifestations [ 15 ]. The reasons why the virus was not reported in significant outbreaks until the beginning of the 21st century are unknown [ 16 ].…”
Section: Introductionmentioning
confidence: 99%